Lifestyle, behaviour, and environmental modification for the management of patients with inflammatory bowel diseases: an International Organization for Study of Inflammatory Bowel Diseases consensus. (July 2022) - Ananthakrishnan, Ashwin N; Kaplan, Gilaad G; Bernstein, Charles N; Burke, Kristin E; Lochhead, Paul J; Sasson, Alexa N; Agrawal, Manasi; Tiong, Jimmy Ho Tuan; Steinberg, Joshua; Kruis, Wolfgang; Steinwurz, Flavio; Ahuja, Vineet; et al.
Summary: Environmental and lifestyle factors play an important role in the natural history of Crohn's disease and ulcerative colitis. A group of international experts from the International Organization for the Study of Inflammatory Bowel Diseases voted on a series of consensus statements to inform the management of inflammatory bowel disease (IBD). The recommendations include avoiding traditional cigarette smoking in patients with Crohn's disease or ulcerative colitis, screening for symptoms of depression, anxiety, and psychosocial stressors at diagnosis and during flares (with referral to mental health professionals when appropriate), and encouraging regular physical activity as tolerated. Patients using dietary approaches for treatment of their IBD should be encouraged to adopt diets that are best supported by evidence and involve monitoring for the objective resolution of inflammation. We recommend formal assessment for obesity and nutritional deficiencies, and patients should be encouraged to maintain a normal body-mass index. A shared decision-making approach to contraception should include the consideration of IBD-related factors, and risk factors for venous thromboembolism. Long-term or frequent use of high-dose non-steroidal anti-inflammatory drugs should be avoided. For primary prevention of disease in the offspring of patients with IBD, we recommend avoiding passive exposure to tobacco, using antibiotics judiciously, and considering breastfeeding when able.